A pastoral evaluation on the issue of ‘vat en sit’ with special reference to the Black Reformed Churches of South Africa - David K. Semenya (HTS Teologiese Studies/Theological Studies, 2016)
This article attempts to investigate and give practical guidelines to the church councils of the mainly Black Reformed Churches in South Africa and also to the couples and families involved in vat en sit relationship. Vat en sit is now becoming a common thing in South Africa. This however does not only affect the black members in the Reformed Churches in South Africa but moreover affect the family structures of the society. Therefore the aim of this article is to find out why in most cases couples opt for vat en sit relationship and also how the church councils could be assisted in dealing with the issue of vat en sit.   The Biblical overview regarding the issue of vat en sit will be discussed and thereafter the practical guidelines be given in order to help both the church councils; the couples in the vat en sit relationship and also their families.